Expression and distribution of ectonucleotidases in mouse urinary bladder. - Weiqun Yu; Simon C Robson; Warren G Hill (PLoS ONE)
Background Normal urinary bladder function requires bidirectional molecular communication between urothelium, detrusor smooth muscle and sensory neurons and one of the key mediators involved in this intercellular signaling is ATP. Ectonucleotidases dephosphorylate nucleotides and thus regulate ligand exposure to P2X and P2Y purinergic receptors. Little is known about the role of these enzymes in mammalian bladder despite substantial literature linking bladder diseases to aberrant purinergic signaling. We therefore examined the expression and distribution of ectonucleotidases in the mouse bladder since mice offer the advantage of straightforward genetic modification for future studies. Principal findings RT-PCR demonstrated that eight members of the ectonucleoside triphosphate diphosphohydrolase (NTPD) family, as well as 5'-nucleotidase (NT5E) are expressed in mouse bladder. NTPD1, NTPD2, NTPD3, NTPD8 and NT5E all catalyze extracellular nucleotide dephosphorylation and in concert achieve stepwise conversion of extracellular ATP to adenosine. Immunofluorescent localization with confocal microscopy revealed NTPD1 in endothelium of blood vessels in the lamina propria and in detrusor smooth muscle cells, while NTPD2 was expressed in cells localized to a region of the lamina propria adjacent to detrusor and surrounding muscle bundles in the detrusor. NTPD3 was urothelial-specific, occurring on membranes of intermediate and basal epithelial cells but did not appear to be present in umbrella cells. Immunoblotting confirmed NTPD8 protein in bladder and immunofluorescence suggested a primary localization to the urothelium. NT5E was present exclusively in detrusor smooth muscle in a pattern complementary with that of NTPD1 suggesting a mechanism for providing adenosine to P1 receptors on the surface of myocytes. Conclusions Ectonucleotidases exhibit highly cell-specific expression patterns in bladder and therefore likely act in a coordinated manner to regulate ligand availability to purinergic receptors. This is the first study to determine the expression and location of ectonucleotidases within the mammalian urinary bladder.